Design and experiment of split-type tracked chassis applied in hilly and mountainous regions - Wang, Wei; Yuan, Lin; Li, Guolong; Zhang, Shiji; Wang, Tiejun; Tang, Chuanyin (International Journal of Agricultural and Biological Engineering, 2025)
The terrain in hilly and mountainous regions is characterized by its discontinuity, constant undulations, and complex environment, leading to significant vibrations and potential tipping over of operating machinery. Traditional crawler chassis face challenges when encountering uneven terrain, with one side possibly being suspended and causing tipping. This study introduces a crawler chassis with a split structure to address this issue. The split design allows for crossing obstacles on one side, enabling better adaptation to the dynamic terrain of hilly and mountainous areas, ultimately maximizing the chassis’ performance. Through research, it was found that the split structure effectively prevents single-sided crawler suspension, allowing for a maximum longitudinal slope angle of 42.3°, transverse slope angle of 27.38°, and a maximum ravine width of 445 mm. The prototype testing confirmed that the chassis can handle slopes of up to 41° on both sides and 30° on one side, with a maximum ravine width of 430 mm. Considering that the typical cultivated land angle in hilly and mountainous regions ranges from 2° to 15°, the designed chassis is well-suited for driving operations in underground farmland within such areas.Keywords: hilly and mountainous machinery, split structure, crawler powered chassis, complex terrain operations, kinematic analysisDOI: 10.25165/j.ijabe.20251803.9293Citation: Wang W, Yuan L, Li G L, Zhang S J, Wang T J, Tang C Y. Design and experiment of split-type tracked chassis applied in hilly and mountainous regions. Int J Agric & Biol Eng, 2025; 18(3): 63–72.